An Empirical Analysis of the Impact of Bank Credit on the Manufacturing Sector Output in Nigeria (1986 - 2016) - ELIJAH, Sunday (Journal of Economics Library, 2019)
Abstract. This study examined the impact of bank credits on manufacturing sector outputs in the deregulated Nigerian economy for the sample period 1986-2016. The data collected were analysed using Autoregressive Distributed Lag (ARDL) models. It was found out that banks credits contributed positively to manufacturing sector output in both short-run and long-run. For causality relationship, EXR, SAV and LR granger cause MSO. Hence, the main determinants of MSO are EXR, SAV and LR. Therefore, it was recommended amongst other things, that the Central Bank and other monetary authorities alike should make policy that will lead to increase in bank credit to the manufacturing sector. As this will play a catalytic role for growth in the sector in particular and the economy in general. Keywords. Bank credit, manufacturing sector, Autoregressive Distributed Lag Model, Bound Test, Lending rate. JEL. E51, L16, F31.